An analysis of the impact of child support grant on teenage fertility rate in South Africa - Mokoma, Tebogo Patrick (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil (Industrial Psychology))--Stellenbosch University, 2008.